1990
DOI: 10.1080/19388079109558038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of issue‐related attitude on readers’ comprehension and judgments of unbiased text

Abstract: To learn maximally from texts centering on controversial topics, readers must suspend attitudinal biases in the interest of objectivity. The present study examines the extent to which issue-related attitudes influence readers' comprehension and retention of information presented in an impartial text. It expands upon previous research that has yielded equivocal findings by considering readers' (a) ego-involvement with the issue, (b) prior knowledge, and (c) purpose for reading. In an immediate and delayed recal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 27 publications
0
12
2
Order By: Relevance
“…Thus, the negative effect of emotional involvement in previous research may originate in background knowledge intrusions. Like Fortner and Henk (1990) and Gaskins (1996), our results showed that students relied on their background knowledge when they read the emotional version, but in our case, the elicited emotional involvement seemed to lead to greater engagement and better comprehension, even though it also was accompanied by more background knowledge intrusions. In fact, emotional involvement seemed to rely on prior knowledge as indicated by the fact that for some of the topics, low background knowledge led to a negative effect of emotions on comprehension, not a positive one.…”
Section: Discussion and Study Significancecontrasting
confidence: 58%
“…Thus, the negative effect of emotional involvement in previous research may originate in background knowledge intrusions. Like Fortner and Henk (1990) and Gaskins (1996), our results showed that students relied on their background knowledge when they read the emotional version, but in our case, the elicited emotional involvement seemed to lead to greater engagement and better comprehension, even though it also was accompanied by more background knowledge intrusions. In fact, emotional involvement seemed to rely on prior knowledge as indicated by the fact that for some of the topics, low background knowledge led to a negative effect of emotions on comprehension, not a positive one.…”
Section: Discussion and Study Significancecontrasting
confidence: 58%
“…One consideration that helps explain the conflicting results of attitude-memory research is the confounding effect of prior knowledge (Fortner & Henk, 1991;Reutzel & Hollingsworth, 1991). When subjects' prior knowledge regarding a target issue has been controlled (Fitzgerald & Ausubel, 1963;Henk & Holmes, 1988;Reutzel & Hollingsworth, 1991;Waly & Cook, 1966), the selective recall hypothesis has only been partially confirmed on one occasion (Reutzel & Hollingsworth, 1991).…”
Section: Research Related To Emotional Involvement: Attitudes and Egomentioning
confidence: 99%
“…However, until Smith and Jamieson's (1972) study had been completed, ego involvement had never been measured and controlled in a research study on attitudes and memory. It is also noteworthy that since 1972, there are only two published studies of the selective recall hypothesis that have attempted to measure and control ego involvement (Fortner & Henk, 1991;Spiro & Sherif, 1975). Thus, Roberts's (1985) comment that the effect of ego involvement on memory has "yet to be adequately explored" (p. 236) still seems warranted.…”
Section: Research Related To Emotional Involvement: Attitudes and Egomentioning
confidence: 99%
See 2 more Smart Citations